Simultaneous bifocal and asymptomatic intramuscular nodular fasciitis of the thigh: A case report - Sukpanichyingyong, Sermsak (Clin Case Rep, 2020)
Nodular fasciitis (NF) is a rapid‐growth benign that is misdiagnosed as sarcoma and leads to overtreatment. The spontaneous regression of NF is a possible phenomenon. “Wait and see” ideal is one of the treatment strategies of NF.